IMPROVEMENT OF THE COMBINED SYSTEM OF ELECTRICITY GENERATION - VASHCHYSHAK, IRYNA; TSYKH, VITALII (Herald of Khmelnytskyi National University. Technical sciences, 2022)
An urgent problem today is the need for uninterrupted and reliable energy supply of buildings and structures using alternative energy. Theoretical research was conducted in order to create a new technology of electricity generation by combining the capabilities of renewable energy sources, namely solar and hydropower. To confirm the possibility of creating a new technology of electricity generation, scientific studies of the properties of heat pipes were conducted. The possibilities of generating electricity from the energy of heated steam, which arises in the process of evaporation and movement of the coolant inside the heat pipe, are estimated. The source of energy for the evaporation process is hot water from the solar collector, which is forcibly supplied to the evaporation zone by a pump. The source of electricity for the operation of the pump and auxiliary equipment and means for cooling the evaporation zone of the heat pipe are solar panels, placed in such a way as to create a constant shadow on the surface of the heat pipe. The use of hot water from the solar collector as a heat source for the operation of such a heat pipe has made it possible to create a new technology for generating electricity with high productivity. Based on the theoretical research, the structure of the combined system of electricity generation is proposed, in which the impeller of the turbine is placed inside the heat pipe, and its heating is carried out by solar collectors, which increased the efficiency of renewable energy sources. The functional scheme of the combined system of generation of the electric power is developed and the principle of its work is resulted. The main theoretical dependences are selected and the parameters of the elements of such a combined generation system are calculated.